Nanocarriers Provide Sustained Antifungal Activity for Amphotericin B and Miltefosine in the Topical Treatment of Murine Vaginal Candidiasis - de Bastiani, Fernanda Walt Mendes da Silva; Spadari, Cristina de Castro; de Matos, Jenyffer Kelly Rocha; Salata, Giovanna Cassone; Lopes, Luciana Biagini; Ishida, Kelly (Frontiers in Microbiology, 2020)
Topical drug administration is frequently used for the treatment of vaginal candidiasis; however, most formulations using this route do not provide prolonged drug release. Our aim was to evaluate the antifungal efficacy of amphotericin B (AMB) and miltefosine (MFS) incorporated in nanocarriers for sustained drug release, in a murine model of vaginal candidiasis. AMB and MFS were incorporated in different topical formulations, namely: conventional vaginal cream (daily dose for 6 days; MFS-CR and AMB-CR groups), microemulsion that transforms into a liquid crystalline gel in situ (single dose, or in 3 doses, every 48 h; AMB-ME and MFS-ME groups) and alginate nanoparticles (single dose; MFS-AN group). Formulations were administered intravaginally in BALB/c female mice 24 h post-infection by Candida albicans yeasts. On the 7th day post-infection the animals were euthanized for mycological and histological analyses. Formulation persistence in the vaginal canal was assessed for 7 days by in vivo imaging, using nanocarriers labeled with Alexa-Fluor 647. AMB-ME(3x), MFS-ME(3x) and MFS-AN(1x) formulations were able to control fungal infection at comparable levels to those vaginal cream formulations. Notably, a single dose of MFS-AN was sufficient to reduce the fungal burden as effectively as MFS-ME(3x) and MFS-CR(6x). In vivo imaging showed that nanocarriers allowed prolonged antifungal activity by intravaginal administration reducing drug administration frequency. Therefore, AMB and MFS incorporated into a microemulsion and MFS encapsulated in alginate nanoparticles could be effective therapeutic alternatives for vaginal candidiasis, likely due to the sustained antifungal activity provided by these nanocarriers.